Outcome of Acromio-Clavicular joint dislocation operated using clavicle hook plate - Prajapati, Akesh; Sitaula, Jyoti; Sharma, Bishnu Dev; Shrestha, Sujit; Pant, Pujan; Rijal, Sanjeev (Journal of Chitwan Medical College, 2018)
Rockwood classification of AC joint dislocation is generally accepted worldwide. Treatment of Rockwood Type 1 and 2 AC joint is non-operative while all authors advocate operative treatment for Rockwood Type 4 and 5 AC joint dislocations. Thirty consecutive patients who underwent operation for acromioclavicular joint dislocation using clavicle hook plate from June 2015 were studied. The dislocations ranged from Rockwood type III to type V. Average follow up time was fourteen months ranging from four to twenty-four months. The outcome was measured using University of California Los Angeles (UCLA) shoulder score. All-the patient had good to excellent result.